EXPERIENCE OF CLINICAL DIAGNOSIS OF PERSISTENT POSTURAL-PERCEPTUAL VERTIGO AT AN OUTPATIENT APPOINTMENT - Наталья Анатольевна Ивонина; Константин Борисович Петров; Сергей Николаевич Филимонов (Медицина в Кузбассе, 2021)
Dizziness, as a clinical symptom, is a subjective phenomenon, which determines the complexity of objective diagnosis. At a specialized neurovestibular reception, the doctor's task becomes to establish whether dizziness is systemic (vestibular) or not systemic, which determines the further tactics of patient management. The existing clinical algorithm for studies of the vestibular system, including oculomotor reactions, as well as standing and walking, can reliably establish the nature of the subjective phenomenon of dizziness. To establish the psychogenic nature of complained complaints of dizziness, it is mandatory to conduct an investigation of the emotional background on appropriate scales. The aim of this study was to identify the incidence of persistent postural-perceptual dizziness in patients with specialized neurovestibular administration. As a result of the study, it was found that psychogenic dizziness occurs in 20.2 % of patients, i.e. every fifth patient at the reception. In the absence of oculomotor reactions, features of violations of the statodynamic function are noted: gait changes, ataxia, easily eliminated with cognitive loading, changes in statics during vision deprivation. Conducting research on the Hospital Anxiety and Depression Scale for such patients allows timely diagnosis of PPPD and the initiation of adequate rehabilitation therapy.